Early childhood education in times of pandemic: an experience report - Silva, Alessandra Batista da; Metzner, Andreia Cristina [UNESP] (Fundacao Univ Tocantins, 2022)
This article consists of the experience report of a kindergarten teacher working in a municipal public school located in the interior of the state of Sao Paulo. This study aimed to present the strategies used to maintain the bond with the children and the ways to elaborate the activities in this period of non-presential classes, due to the Covid-19 pandemic. For this, a descriptive study of an experience lived in a class of children between four and five years of age was carried out. It was noted that teachers had to reinvent themselves, overcome technological difficulties, research other types of activities, exchange information and share tasks with peers in order to make remote teaching more attractive and accessible to young children.
Keywords: Early Childhood Education; Pandemic; Remote Teaching